The Palgrave Handbook of the European Administrative System
XXI, 511 p.
Keywords: Drawing on research from the administrative sciences and using organizational, institutional and decision-making theories, this volume examines the emerging bureaucratic framework of the EU and highlights that analyzing the patterns and dynamics of the EU's administrative capacities is essential to understand how it shapes European public policy.